Montrichardia linifera (Arruda) Schott promotes accelerated wound healing in vitro: a promising healing - Aline Costa Bastos; Aline Costa Bastos; Maurício Ferreira Gomes; Maurício Ferreira Gomes; W. B. S. Pinheiro; Anderson de Santana Botelho; Raimundo Junior da Rocha Batista; Cristine Bastos do Amarante; Taia Maria Berto Rezende; Yasmin Cunha da Silva; Ananda da Silva Antonio; Henrique Marcelo Gualberto Pereira; et al. (Frontiers in Pharmacology)
IntroductionMontrichardia linifera (Arruda) Schott (M. linifera) is commonly used by Amazonian riverine communities for the treatment of skin ulcers, although its effects as a wound healer have never been evaluated until now. Therefore, the in vitro wound-healing activity of the extracts from the stem and petiole of M. linifera was investigated for the first time.MethodsThe extracts were characterized by chromatography coupled with spectroscopic or spectrometric methods (HPTLC-UV and UHPLC-MS), and free radical scavenging was verified using bioautography with the DPPH radical. Cytotoxicity was evaluated through the MTT method, and a scratch assay was employed to assess cell migration, while in vitro cell proliferation was evaluated through immunofluorescence for BrdU-positive cells.ResultsChemical characterization revealed the presence of 13 metabolites in ESML and EPML extracts. Analytical analysis of the extract demonstrated the elimination of free radicals by autobiography. The extracts did not demonstrate cytotoxicity in fibroblasts and cell migration and proliferation were, significantly, increased reducing the wound area in vitro.ConclusionThus, it was observed that the extracts from the stem and petiole of M. linifera possess potential wound-healing effects in fibroblasts in vitro. This is a pioneering study that provides insights for future studies on the mechanisms of action of this species, in addition to validating the ethnopharmacological knowledge of this species used in the Amazon.